Pelatihan dan Pendampingan Pemanfaatan Media Digital untuk Medukung Peningkatan Pemasaran Produk UKM di Desa Uteunkot Kota Lhokseumawe - Sahputra, Ilham; Fakhrurrazi; Devi Irwansyah; Angelina, Difa; A Zohra, Siti Fatimah (AJAD : Jurnal Pengabdian kepada Masyarakat, 2023)
The use of digital media by MSMEs, which is increasingly competitive and growing rapidly, requires Small and Medium Enterprises (SMEs) to implement effective and efficient marketing strategies. The use of digital media is very important in marketing SME products in the digital era. However, the problem faced is the lack of knowledge and skills of Uteunkot village residents in utilizing digital media as a marketing tool. Meanwhile, training and mentoring are effective solutions for increasing the use of digital media to support the growth and success of SMEs. This service aims to empower SMEs in Uteunkot Village through digital media to support increased marketing of SME products. The training material covers the use of social media, both content creation and online advertising strategies. The results of the Digital Media Utilization Training and Assistance service showed that 88% and 12% of respondents were satisfied with implementing the service activities. Then, the results of the solution's suitability are expected by partners to increase their productivity and market access using digital technology and be able to compete better in an increasingly competitive market.